"Fat" Chicks Who Run: Stigma Experienced by "Overweight" Endurance Athletes. (February 2018) - Inderstrodt-Stephens, Jill; Acharya, Lalatendu
Research on "overweight" and "obese" populations is extensive, but little of this research specifically addresses the "obese" or "overweight" amateur endurance athlete. Amateur endurance athletes often have bodies that defy the stereotype of the typical marathoner, swimmer, or triathlete. As a result, these athletes can experience stigma, both within their sporting communities as well as in the workplace, at home, and from spectators at athletic events. In an effort to discover what brings "overweight" adults to endurance sports and to recognize the barriers that they encounter to stay active in sports, this study seeks to identify the types of stigma that "overweight" endurance athletes face, the effects stigma has on their physical and mental health, and the effects stigma has on their participation in sports. Six amateur endurance athletes who identify as "overweight" were interviewed, and data were coded using Owen's interpretive themes framework. Participants were found to experience stigma in being members of the "back of the pack, " in their entry into endurance sports, and in the lack of competition-quality clothing available for larger body types. Participants experienced negative physical and mental health outcomes as they internalized the stigma messages received during training and racing. No negative effects on participation were observed.